Assessment of groundwater recharge along the Guarani aquifer system outcrop zone in São Paulo State (Brazil): an important tool towards integrated management - Santarosa, Lucas Vituri [UNESP]; Gastmans, Didier [UNESP]; Sitolini, Tatiana Penteado [UNESP]; Kirchheim, Roberto Eduardo; Betancur, Sebastian Balbin [UNESP]; de Oliveira, Marcelo E. Dias [UNESP]; Campos, José Cláudio Viégas [UNESP]; Manzione, Rodrigo Lilla [UNESP] (Springer Nature, 2021)
The quantification of the groundwater recharges represents useful and important information for water resource management. The volumes of infiltrated water are essential to maintain water storage in aquifers, as well as to the discharge of groundwater towards the rivers, especially in tropical areas. The outcrop zones of the Guarani Aquifer System (GAS) in São Paulo state (Brazil) are considered as their most important recharge areas; therefore, knowledge about recharge rates and processes is essential. They are also highly vulnerable to groundwater contamination, another important reason to protect them. This study aimed to estimate spatial and temporal variations of groundwater recharge in the mentioned GAS outcrop zones. Recharge rates were estimated using the Spatial Recharge (SR) method and then compared to other two traditional methods (base flow separation and water table fluctuation method). The SR method uses the spatial distribution of the evapotranspiration and rainfall from GLDAS and TRMM databases and the runoff after the Soil Conservation Service (SCS) empirical method. All three methods revealed similar estimates for groundwater recharge, ranging from 150 to 370 mm year−1 (about 17% of the total rainfall). Despite its intrinsic limitations, the SR method allowed robust recharge estimation with ability to cope with spatial and temporal variations, as well, especially in areas lacking hydrological monitoring programs. The SR method provides valuable information for water management policymakers and stakeholders to minimize impacts related to climatic variations and inappropriate land use on recharge processes.
Keywords: Aquifer recharge; GIS-based recharge; Guarani aquifer system; Remote-sensing data